Characteristics of the Ontario Neurodegenerative Disease Research Initiative cohort. Issue 1 (30th March 2022) - Sunderland, Kelly M.; Beaton, Derek; Arnott, Stephen R.; Kleinstiver, Peter; Kwan, Donna; Lawrence‐Dewar, Jane M.; Ramirez, Joel; Tan, Brian; Bartha, Robert; Black, Sandra E.; Borrie, Michael; Brien, Donald; et al.
Abstract: Introduction: Understanding synergies between neurodegenerative and cerebrovascular pathologies that modify dementia presentation represents an important knowledge gap. Methods: This multi‐site, longitudinal, observational cohort study recruited participants across prevalent neurodegenerative diseases and cerebrovascular disease and assessed participants comprehensively across modalities. We describe univariate and multivariate baseline features of the cohort and summarize recruitment, data collection, and curation processes. Results: We enrolled 520 participants across five neurodegenerative and cerebrovascular diseases. Median age was 69 years, median Montreal Cognitive Assessment score was 25, median independence in activities of daily living was 100% for basic and 93% for instrumental activities. Spousal study partners predominated; participants were often male, White, and more educated. Milder disease stages predominated, yet cohorts reflect clinical presentation. Discussion: Data will be shared with the global scientific community. Within‐disease and disease‐agnostic approaches are expected to identify markers of severity, progression, and therapy targets. Sampling characteristics also provide guidance for future study design.